Translating Social Constructivism into English Language Teaching: Some Experiences - Paliwal, A.K. (JOURNAL OF INDIAN EDUCATION, 2009)
This paper is based on the author’s own experiences generated through the actual classroom situations involving constructivist approach to English Language Teaching (ELT).The author of the paper holds the view that language is both a cognitive constructivist and social constructivist process and product. It is cognitive constructivist in the sense that learners construct their own language and its grammar. It is social constructivist in that it is only in, for and through society that language is used. No human language may evolve, function, operate, develop and be dynamic without social interaction. Language encompasses all forms of constructivism. However, its framework is largely social which helps the learners in acquiring/learning the rudimentary language skills (LSRW), grammatical / linguistic and communicative competence. This paper discusses some social constructivist activities and tasks to make the main point clear.